Accident Risk Indices Of Malaysia’s Firefighters Working in 12 And 24 Hours Shift Works - Sharifah, Osman; Ismail, Bahari; Kadir, Arifin; Wan Mohd Nor, Hj Ibrahim; Chen, Teck Foong (2012)
Work shift has been shown to correlate with accident rates. Understanding of such correlation is pertinent especially among emergency response personnel since the decisions that they make determines not only the outcome of their responses but also the risk of accidents to themselves. A questionnaire data derived study used together with a semi quantitative risk analysis method was adopted to estimate the levels of accident risks between firefighters working on two shifts. Two hundred and forty eight Malaysia's fire and Rescue Department firemen from 24 fire stations working on shifts were selected as respondents.